The rs7404339 AA Genotype in CDH5 Contributes to Increased Risks of Kawasaki Disease and Coronary Artery Lesions in a Southern Chinese Child Population - Wang, Yishuai; Lin, Kun; Zhang, Linyuan; Lin, Yueling; Yu, Hongyan; Xu, Yufen; Fu, Lanyan; Pi, Lei; Li, Jinqing; Mai, Hanran; Wei, Bing; Jiang, Zhiyong; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background Kawasaki disease (KD) is an acute, self-limited febrile illness of unknown cause. And it predominantly affects children <5 years and the main complication is coronary artery lesion (CAL). Studies demonstrated that vascular endothelial cells (VECs) played a very important role in the CAL of KD. VE-cad encoded by CDH5 may exert a relevant role in endothelial cell biology through controlling the cohesion of the intercellular junctions. The pathogenesis of KD remains unclear and genetic factors may increase susceptibility of KD. However, the relationship between CDH5 polymorphisms and KD susceptibility has not been reported before. The present study is aimed at investigating whether the rs7404339 polymorphism in CDH5 is associated with KD susceptibility and CAL in a southern Chinese child population. Methods and Results We recruited 1335 patients with KD and 1669 healthy children. Each participant had supplied 2ml of fresh blood in the clinical biologic bank at our hospital for other studies. Multiplex PCR is used to assess the genotypes of rs7404339 polymorphism in CDH5. According to the results, we found significant correlated relationship between rs7404339 polymorphism in CDH5 and KD susceptibility [AA versus GG: adjusted odds ratio (OR) = 1.43, 95% confidence interval (CI) =1.00-2.05; p = 0.0493; recessive model: adjusted OR = 1.44, 95% CI =1.01-2.06, P = 0.0431]. In further stratified analysis, we found that children younger than 60 months (adjusted OR = 1.46, 95% CI = 1.01-2.10; p = 0.0424) and male (adjusted OR = 1.70, 95% CI = 1.09-2.65; p = 0.0203) with the rs7404339 AA genotype in CDH5 had a higher risk of KD than carriers of the GA/ GG genotype. Furthermore, stratification analysis revealed that patients with the rs7404339 AA genotype exhibited the significantly higher onset risk for CAL than carriers of the GA/ GG genotype (adjusted age and gender odds ratio= 1.56, 95% CI=1.01-2.41; P=0.0433). Conclusion Our study has shown a significant relationship between rs7404339 AA genotype in CDH5 and KD risk in children younger than 60 months and male. In addition, we confirmed the rs7404339 AA genotype in CDH5 increased risk of CAL in a Southern Chinese Child Population.